AUTHENTICITY CRITERIA IN CONSERVATION OF SACRED BUILDINGS - Poloz, Iryna; Alho, Carlos (European Scientific Journal, ESJ, 2015)
Religious buildings are subject to change throughout the life. So we should know how authenticity affects the conservation of sacred buildings? Authors based on case studies of sacred buildings in Ukraine to understand the best practices for further definition of the authenticity to better maintain the sacred buildings. Taking in consideration the different interdisciplinary views of Europe in Conservation and research materials of sacred buildings in Ukraine, this research aims for a consensus about the concept of the authenticity criteria and a way to improve the practice into conservation of sacred building. The results show that "authenticity criteria" are similar to “sustainable development” and it is different depending on the geographical location and culture.